(untitled) (MAUSAM, 1970)
The mean hourly rainfall for 15 selected stations having the data for the period 1948-1965 has been studied to find out the diurnal variation of rainfall in India. An attempt has been made to explain the different patterns observed on the basis of the models given by the previous workers.